Analysis of the stress level of resident physician education program specialist in Obstetrics and Gynecology Andalas University in 2020 - Fajri, Ari Fuad; Utama, Bobby Indra; Hardisman, Hardisman (Andalas Obstetrics And Gynecology Journal, 2022)
Introduction:The Specialist Doctor Education Program (PPDS) is one of the academic education of general practitioners and is known as a resident doctor to become a specialist and is at the forefront ofhealth services. Resident doctors are expected to be flexible clinicians, educators, researchers, andadministrators by the end of their residency training. It often requires stressful hard work, and is oftenreported as a cause of burnout, anxiety, depression, anger, irritability, anxiety, sleep deprivation,fatigue, substance abuse, and psychosocial problems. One of the problems that often occurs with residents is long working hours. Based on the working hours regulation adopted in the UK since 1998, namely the European Working Time Directive (EWTD) and a policy change in 2007 and 2009 called The New Deal, the working hours of resident doctors to achieve optimal performance is 56 hours per week. In the initial survey of 10 PPDS Obgin Unand residents, network station residents still had to carry out their duties 24 hours a day for 1 month in the hospital. Except for applying for certain permits. If you add up, the average working hours in 1 week is more than 60 working hours. Objective: This study aims to determine the stress level of resident doctors in the Education Program ofÂ  Obstetric and Gynecology Specialist, Andalas University in 2020Methods: This research is a quantitative study followed by qualitative method using an explanatory design. Data was taken using the triangulation method. The data was taken from questionnaires, Focus Group Discussion (FGD), and document review from Obstetric and Gynecology residents of all semester at Andalas University.Results: The highest stress level in the Obstetric and Gynecology residents of Andalas University in 2020 was 60.3% at moderate level, there was a relationship between stress levels with graduation and semester. The highest stress domain is ARS (Academic Related Stressor) and SRS (Social Related Stressor).Conclusion: the stress level in the Obstetric and Gynecology residents of Andalas University in 2020 is at a moderate level, and the highest stress domain is ARS (Academic Related Stressor) and SRS (Social Related Stressor).Keywords: Resident Doctor; Obstetric and Gynecology; stress